Interplay between metabotropic glutamate type 4 and adenosine type 1 receptors modulate synaptic transmission in the cerebellar cortex - Bossi, Simon; Daniel, Hervé; McLean, Heather (Frontiers in Pharmacology, 2024)
The synapses between parallel fibers and Purkinje cells play a pivotal role in cerebellar function. They are intricately governed by a variety of presynaptic receptors, notably by type 4 metabotropic glutamate (mGlu4) receptors and type 1 adenosine (A1) receptors both of which curtail glutamate release upon activation. Despite their pivotal role in regulating synaptic transmission within the cerebellar cortex, functional interactions between mGlu4 and A1 receptors have remained relatively unexplored. To bridge this gap, our study delves into how mGlu4 receptor activity influences A1 receptor-mediated alterations in excitatory transmission. Employing a combination of whole-cell patch clamp recordings of Purkinje cells and parallel fiber presynaptic fluorometric calcium measurements in acute rat and mouse cerebellar cortical slices, our results reveal functional interactions between these receptor types. These findings hold implications for understanding potential roles of these presynaptic receptors in neuroprotection during pathophysiological conditions characterized by elevated glutamate and adenosine levels.